The interrelated impacts of credit access, market access and forest proximity on livelihood strategies in Cambodia. (July 2022) - Felkner, John S.; Lee, Hyun; Shaikh, Sabina; Kolata, Alan; Binford, Michael
Highlights: Analysis of the interactions of financial credit, market access and forest access on household expenditures and livelihood incomes in Cambodia. Credit significant with off-farm business, land, and livestock incomes; market access with off-farm business incomes; forest access with income and expenditures. Forest access significant with gross incomes and expenditures when controlling for market and credit access. Credit most important for gross income and expenditures; market access for off-farm and agricultural incomes. Interaction effects are statistically significant; forest and market access, and credit and market access, have synergistic impacts on incomes. Abstract: Livelihood diversification strategies in developing countries are influenced by access to financial credit, to markets and to forests. Understanding their interrelated impacts has important implications for development policy, for market access, credit provision, and forest conservation. Using a survey of 2, 417 households in 64 villages in four Provinces in Cambodia and satellite data on forest extent, we test hypotheses and quantify the relative contributions and first-order interactions effects of market and road access, forest access, and formal and informal financial credit access on household expenditures and livelihood incomes. We test hypotheses about their statistical interactions, their relative contributions to incomes, and how their effects differ within and outside the Mekong River floodplain. Market and road access are significant with gross income and expenditures, as well as portfolio shifts to off-farm business activities. Forest access contributes significantly to gross income and expenditures. Credit utilization is significant with gross income, expenditures, off-farm business, and livestock activities. Households below the poverty line use financial credit primarily for consumption and agricultural investments, but above the poverty line for business investment and purchasing assets. Market access and financial credit are more important for incomes in the Mekong floodplain area, while forest access is more important outside it. Using dominance analysis, we find that financial credit contributes more than market or forest access to gross income, expenditures, and livestock income. However, market access is more important than credit for off-farm, on-farm and crop incomes, and forest access contributes more to gross income than formal credit access. We also test for first-order interactions between these effects and find they are statistically significant, confirming a synergistic interaction between credit, market and forest access. Market access improves the impact of credit use, as credit use improves gross and off-farm incomes with improved access to large cities, and improves livestock incomes with improved road access. Forests and roads act synergistically to improve household incomes in areas with good city market access, as forest access contributes more to gross income, expenditures and off-farm incomes in areas with good primary road access, and to on-farm incomes in areas with good secondary road access. Our findings show that market, road, credit and forest effects are interconnected and interdependent, but support each other, and significant interaction effects between forest and market access suggest that policies for poverty reduction and forest conservation should be coordinated with the development of roads to improve potential forest returns.